Penerapan Metode Simulasi Untuk Meningkatkan Hasil Belajar Seni Tari Siswa Di Kelas VIII.6 SMP Negeri 7 Padang - Maryunis Lestari; Yuliasma Yuliasma; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2019)
The article aims to describe the application of simulation methods to improve the learning outcomes of dance in class VIII.6 of SMP Negeri 7 Padang. This type of research is Classroom Action Research (CAR) or Classroom Action Research. The instrument of this study was the researchers themselves and assisted with supporting instruments in the form of observation sheets of student learning activities, knowledge tests (cognitive) and skills tests (psychomotor). The data collection technique used in each cycle is by observing, testing and documenting. The types of data in this study are primary data and secondary data. Student learning outcomes data were analyzed using mean techniques and using individual and group completeness criteria. The results of the study show that the application of simulation learning methods can improve the learning outcomes of Dance VIII.6 grade students at Padang 7 Public Middle School. Learning activities consist of positive activity and negative activity. Positive learning activities are with indicators asking questions, daring to argue, and doing assignments. Negative learning activities that are with indicators do not concern in class and do not go out of class. Learning activities in the first cycle were still low seen in positive activity 62% and negative activity 61%. While the second cycle obtained an average of 85% positive learning activities and negative learning activities 89%. The average learning outcomes in the first cycle were obtained 82 and the average learning outcomes in the second cycle were 89.4. So it was concluded that the application of simulation methods to improve the learning outcomes of Dance in class VIII.6 students at Padang 7 Junior High School had succeeded.